Surface morphology studies of low carbon steel treated in aqueous lignin - Yahya, S.; Othman, N.K.; Daud, A.R.; Jalar, A. (Universiti Kebangsaan Malaysia, 2013)
The effect of corrosion inhibition of low carbon steel in water based medium containing lignin was investigated via weight loss method. The evolution of surface morphology has been carried out for 7 to 42 days via optical microscopy (OM), scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDX) and X-ray photoelectron microscopy (XPS). Immersion of metal specimen without lignin shows that significant increase in the surface roughness. The longer the immersion time, the more the oxide crust formed. The surface degradation of metal specimen was well protected by immersion in lignin solution. A protective layer containing of lignin was formed on the surface of metal specimens after 7 and 21 days immersion. The corrosion inhibition gives about 13 and 53% inhibition for both 7 and 21 days immersion, respectively. The protective layers were spalling and separated from the metal surface after 42 days immersion in lignin solution possibly due to the increase in corrosion attack after long time immersion according to the increase in dissolved oxygen and may also due to the thermal mismatch between oxide and substrate. The adsorption of protective layer containing lignin was temporary adsorbed on the surface.